Genetic diversity and population structure of Euterpe edulis by REML/BLUP analysis of fruit morphology and microsatellite markers - Carvalho,Marina Santos (2020)
Abstract Euterpe edulis is an endemic species of the Atlantic Forest that is threatened by the unsustainable exploitation of palm heart. Fruit management is an alternative to overcome this problem, promoting income generation, preserving the trees in forest remnants and motivating the implementation of farms for commercial production. In this study, the genetic diversity and structure of four natural populations of E. edulis were evaluated using microsatellite markers and six morphological fruit traits, analyzed with and without the REML/BLUP method. The longitudinal diameter had the strongest influence on the differentiation of genotypes. The genetic differentiation among populations was low and inbreeding was detected within populations among sites. Molecular and morphological data indicated high genetic diversity in the E. edulis populations. The REML/BLUP analysis increased the accuracy of morphology-based estimates of genetic diversity, thus contributing to improve breeding strategies for fruit quality and genetic conservation by use in E. edulis.